Nucleation as a rate-determining step in catalytic gas generation reactions from liquid phase systems - Solymosi, Thomas; Geißelbrecht, Michael; Mayer, Sophie; Auer, Michael; Leicht, Peter; Terlinden, Markus; Malgaretti, Paolo; Bösmann, Andreas; Preuster, Patrick; Harting, Jens; Thommes, Matthias; Vogel, Nicolas; et al. (Science Advances, 2022)
The observable reaction rate of heterogeneously catalyzed reactions is known to be limited either by the intrinsic kinetics of the catalytic transformation or by the rate of pore and/or film diffusion. Here, we show that in gas generation reactions from liquid reactants, the nucleation of gas bubbles in the catalyst pore structure represents an additional important rate-limiting step. This is highlighted for the example of catalytic hydrogen release from the liquid organic hydrogen carrier compound perhydro-dibenzyltoluene. A nucleation-inhibited catalytic system produces only dissolved hydrogen with fast saturation of the fluid phase around the active site, while bubble formation enhances mass transfer by more than a factor of 50 in an oscillating reaction regime. Nucleation can be efficiently triggered not only by temperature changes and catalyst surface modification but also by a mechanical stimulus. Our work sheds new light on performance-limiting factors in reactions that are of highest relevance for the future green hydrogen economy.